Peculiarities of the Evaluation of Behavior by Adolescents - Martišauskienė, Eivyda (Acta Paedagogica Vilnensia, 1996)
Evaluation of behaviour is a complicated phenomenon. It is the integral and dynamic trait of personality. It is expressed by the ability to state the very fact of behaviour; ability to describe the situation in which the act of behaviour took place; ability to give moral evaluation of the behaviour of others; ability to give moral evaluation of one’s own behaviour. The article describes the research in which over 800 pupils of 5-9th forms participated. The research was aimed at revealing the abilities of evaluation by pupils mentioned above. The results show that level of abilities of most pupils is insufficient. The ability to state the very fact of behaviour was developed most, the ability to give moral evaluation to own behaviour – developed least.
Keywords: Adolescents; evaluation of behavior; moral education; moral evaluation; values.